Serious Games Development and Applications Second International Conference, SGDA 2011, Lisbon, Portugal, September 19-20, 2011. Proceedings - Ma, Minhua; Fradinho Oliveira, Manuel; Madeiras Pereira, João.; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the Second International Conference on Serious Games Development and Applications, SGDA 2011, held in Lisbon, Portugal, in September 2011
Keywords: Interactive multimedia -- Congresses; Educational games -- Congresses; Computer games -- Congresses; Electronic book